2018
DOI: 10.1101/283051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new view of dorsal visual cortex in macaques revealed by submillimeter fMRI

Abstract: Macaque dorsal occipital cortex is generally thought to contain one elongated third-tier area, V3d, extending along most of the rostral V2d border. In contrast, our submillimeter retinotopic fMRI maps (0.6 mm isotropic voxels, achieved by implanted phased-array receive coils) consistently show three sectors anterior to V2d. The dorsal (mirror-image) sector complies with the traditional V3d definition, and the middle (non-mirror image) sector with V3A. The ventral (mirror-image) sector bends away from V2d, as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…However, we also found that this representation merged directly into a representation of the upper quadrant near the midline, thereby forming a single representation of the peripheral visual field. Complementing the results of a recent study of the lateral part of the third tier complex (Zhu and Vanduffel, 2018), these findings point to a reinterpretation of the areas rostral to dorsal V2 in the macaque.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, we also found that this representation merged directly into a representation of the upper quadrant near the midline, thereby forming a single representation of the peripheral visual field. Complementing the results of a recent study of the lateral part of the third tier complex (Zhu and Vanduffel, 2018), these findings point to a reinterpretation of the areas rostral to dorsal V2 in the macaque.…”
Section: Introductionsupporting
confidence: 78%
“…4A, B, D). However, our recording grid did not include more lateral regions where a more extensive representation of the upper quadrant is reported to exist adjacent to V2 (Zhu and Vanduffel, 2018). Receptive field 5 in Figure 5A exemplifies the upper quadrant invasion in this region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the macaque, it is currently debated whether V2 is adjoined by a single area V3 or multiple third-tier areas (Angelucci et al, 2015; Zhu and Vanduffel, 2018). A recent high-resolution fMRI retinotopy study (Zhu and Vanduffel, 2018) provides strong evidence for at least three (and possibly four or five) third-tier areas in a pattern similar but not identical to New World monkeys in the six hemispheres (3 monkeys) that were studied. In contrast, many fMRI studies in humans point to a simpler arrangement in which a single V3 adjoins most of V2 and lacks a comparable degree of dorso-ventral asymmetry (see SI section 4.1.3).…”
Section: Introductionmentioning
confidence: 99%